New and interesting species of Agaricomycetes from Panama - Reschke, Kai; Lotz-Winter, Hermine; Fischer, Christian W.; Hofmann, Tina A.; Piepenbring, Meike (Phytotaxa, 2021)
Panama forms part of the Central American biodiversity hotspot, one of the most important biodiversity hotspots in the world. While plants are relatively well studied in Panama, the documentation of fungal diversity is still in a pioneer phase. In this publication, four species of Agaricomycetes recently collected in Panama are described as new to science, two in Agaricales, namely Gliophorus roseus and Humidicutis roseorubra, a lichenised species in Cantharellales, called Multiclavula caput-serpentis, and a species in Gomphales, called Gloeocantharellus salmonicolor. These species are described and illustrated. Their phylogenetic affinities are discussed based on morphological characters and molecular phylogenies. Further six species of Agaricales, which have not been reported from Panama before, are presented as new records for the country, along with data on their morphology, ecology and taxonomy.